Adam Smith and Sophie de Grouchy on Education - Markwart, Anna (Studia z Historii Filozofii, 2019)
The paper analyses Adam Smith’s and Sophie de Grouchy’s views concerning education. It addresses both the issues of formal education in institutions for instruction as well as it mentions an informal transfer of values within the family and the society. The brief characteristic of the notions of sympathy and an impartial spectator precedes the discussion of the goals education should serve. It is an individual’s development that is the core issue of the thinkers’ considerations. The benefits for the society, at least in Smith’s case, are important, yet subordinate. Both of the philosophers presented a critique of existing educational institutions. Smith’s views on ways of financing universities and schools are also summarized in the paper. Moreover, a discussion on the issues of educating children and adults is presented, mentioning the importance of universal access to knowledge. It is the idea that people need to achieve the ability to think critically and not to learn the rules (also those of morality) by heart that marks the significance of Smith’s and de Grouchy’s philosophy of education.